Glue Injection Molding For Bamboo Fibre Pot Making Machine - Padan, Cassandra Sulau; Shaari, Muhammad Farid bin (Progress in Engineering Application and Technology, 2022)
Pots are a container that is commonly used to cultivate plants or flowers. Plastic plant pots have disadvantages, such as fading and brittleness when exposed to the sun, and the plastic cracking easily. Whenever plastics pots exposed to the sun can leak chemicals into the soil. Since there are various issues that arise as a result of using plastic pots, such as pollution and its disadvantages, the study encourages the development of biodegradable pots. This material can easily be planted with the plants in the soil, and the container will ultimately dissolve. Thus, this study is to identify the optimum and design of glue injection moulding machine for fibre bamboo pots by using Morphological chart and S.C.A.M.P.E.R method. Both methods identify the generating idea, concept selection mechanism and fabrication process for the glue injection molding process. The methods and procedures used to develop, assess, and examine data in order to get results that may be utilized to support this research are referred to methodology. Through getting the raw materials to testing and analysing the outcomes, the flow chart represented the steps in the process. In conclusion, the finding of this research is important including fabricating knowledge to understanding the development of a new product fabricated and in order to produce an innovative product to increase the production of fibre bamboo pots in the future.